Relationship between maternal reading beliefs, home environment, and mother-child interaction with emergent literacy among young children in Iran - Jafari Sadr, Azimeh (2015)
The objectives of the study had been to determine the relationships between maternal reading beliefs, home environment, mother-child interaction and emergent literacy amongst young children in Iran. Findings of this mixed methods strategy study were based on data collected from 90 children between the ages of 3 and 4 years and their mothers. Data were collected using questionnaires, observation and face to face interview. Children were assessed individually while mothers completed mothers’ reading beliefs inventory. Mother and child interactions were videotaped, and home environment was observed, while mothers were asked to respond to the questions related to their home environment in the questionnaire. Results of the current study indicate that there was no significant relationship between maternal reading beliefs and emergent literacy. However, a positive and significant relationship was found between home environment and emergent literacy among the children. The findings of this study showed that children who were exposed to better home environment, have higher emergent literacy skills. There was also a positive and significant relationship between mother-child interaction and emergent literacy. Children whose mothers had higher scores in storybook reading style in mother-child interaction showed higher emergent literacy skills. The findings also confirmed that there were no significant difference in emergent literacy skills between boys and girls in this study. From the multivariate analysis, the home environment appeared as the strongest predictor of child’s emergent literacy, followed by mother-child interaction. The present study also supported the partial mediation role of mother-child interaction in the relationship between home environment and emergent literacy among young children. For the qualitative analysis, mother-child storybook reading interaction was investigated by observing the interactions that took place between mother and child during reading storybooks. The presentation of the reaction of the child was divided in two categories of reaction, based on whether the child was deemed active or passive. The possible types of activity or passivity in the response of the child depends on the maternal behaviors during storybook reading, such as when the mother used cognitive and emotional aspects in her reading style and methods, during the process of reading storybooks to children who were active. If mothers were more supportive of their children during the process of reading storybooks, the children were more likely to enjoy the activity to a greater degree, particularly if cognitive and emotional aspects had been applied properly during the reading. It would be reasonable to conclude that storybook reading interactions between mother and child had been firmly connected to language and emergent literacy skills. The findings of this study should reveal important implications for promoting and encouraging physical, cognitive, social and behavioral elements in supporting the development of children’s emergent literacy prior to the beginning of formal schooling.Various possibilities regarding the nurturing of emergent literacy were suggested which include encouraging mothers to read with their children, promoting positive interactional behavior between mother and child, and providing advice on the creation of a more conducive home environment.